The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1667/rr1825.1
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to56Fe-Particle Radiation Accelerates Electrophysiological Alterations in the Hippocampus of APP23 Transgenic Mice

Abstract: An unavoidable complication of space travel is exposure to high-charge, high-energy (HZE) particles. In animal studies, exposure of the CNS to HZE-particle radiation leads to neurological alterations similar to those seen in aging or Alzheimer's disease. In this study we examined whether HZE-particle radiation accelerated the age-related neuronal dysfunction that was previously described in transgenic mice overexpressing human amyloid precursor protein (APP). These APP23 transgenic mice exhibit age-related beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…One example is a defect in neurogenesis, which has been documented in response to traditional radiotherapy [38] as well as exposure to 56 Fe particles [5], [7], [39]. In addition to neuronal proliferation defects, impaired cognition could also result from inhibition of long-term potentiation (LTP) [40], an effect which has been reported with 56 Fe particle irradiation in the APP23 transgenic mouse model of AD [41].…”
Section: Discussionmentioning
confidence: 99%
“…One example is a defect in neurogenesis, which has been documented in response to traditional radiotherapy [38] as well as exposure to 56 Fe particles [5], [7], [39]. In addition to neuronal proliferation defects, impaired cognition could also result from inhibition of long-term potentiation (LTP) [40], an effect which has been reported with 56 Fe particle irradiation in the APP23 transgenic mouse model of AD [41].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we (14) and others (13) hypothesized that exposure to radiation may accelerate the onset of neurodegenerative diseases, such as Alzheimer's disease. The common hallmarks of Alzheimer's disease and radiation exposure include oxidative stress markers (15)(16)(17), which have been associated with impaired synaptic plasticity (18,19).…”
mentioning
confidence: 99%
“…Inhibition of neurogenesis could be detected after whole-body irradiation with proton doses as low as 0.5 Gy (28). Although several functional decrements in Alzheimer's disease (29)(30)(31)(32) and in the irradiated brain (14,33) are clearly similar and are likely related, the effects of radiation on other, perhaps less obvious but significant, functional manifestations in Alzheimer's disease have never been tested. For example, the propensity for epileptiform activity (34) and altered oscillatory properties in the local hippocampal networks (35,36) have been described in Alzheimer's disease, but have never been tested in irradiated neuronal tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A certain amount of interest has been given to the potential risks (including AD risks) associated with space travel. A recent report has shown that exposure to high energy 56 Fe 26+ iron nuclei accelerated age-related neurological dysfunction in APP23 transgenic mice overexpressing human APP [99]. Knowing that AD was often described as a process similar to accelerated ageing [100], the authors concluded that exposure to cosmic high-energy particles might accelerate AD-related neurological deficits.…”
Section: Is Ionizing Radiation a Risk Factor For Ad?mentioning
confidence: 99%